TOOLS OF DIVERSIFICATION ACTIVITIES IN THE FORMATION OF A CORPORATE INTEGRATED SYSTEM IN TRADE - Trofymenko , K. V. (The actual problems of regional economy development, 2023)
The topic of the article "Tools of diversification activity in the formation of a corporate integrated system in trade." The purpose of the research is the formation of clearly defined tools for horizontal, vertical and conglomerate diversification and the formation of recommendations for building a corporate integrated system, which corporate trading systems will be able to use in their activities. The study highlighted the importance of diversification activities in today's conditions, characterized its main integration manifestations in the activities of corporate systems in trade activities. The key alternatives when choosing types of strategy (unrelated, combined and related diversification strategies) are presented and the main factors that should be taken into account when choosing them are defined. The key tools and features of the implementation of vertical, horizontal and conglomerate diversification, technological, economic for corporate trade networks in trade are characterized. The concept of standardization of diversification processes and its place in the strategic management system are outlined. In the process of the research, the importance and features of the formation of a corporate integrated structure in the process of carrying out diversification activities of trade networks were determined. The necessity of dividing the corporate integrated system into subsystems of strategic and operational management is clarified. The results of the study present the author's development of the structure and ratio of subsystems of strategic and operational management of the processes of diversification of the corporate integrated structure. The main tools for carrying out diversification activities are presented and characterized. In particular, the advantages and disadvantages of starting a new line of business within an existing enterprise, merger and/or acquisition of capital, creation of strategic partnerships and/or new organizations, application of franchising, investment, etc. are characterized. Three key functions, which are the basis for choosing new types of economic activity other than the main trade activity, have been clarified. It was determined that the issue of mutually coordinated, balanced, effective functioning of all elements of the corporate integrated system is directly correlated with the modernization of management models in corporate trade systems, which is a direction for further research.